Improving nitrogen use efficiency and reducing nitrogen surplus through best fertilizer nitrogen management in cereal production: the case of India and China - Sapkota, Tek Bahadur; Singh, Bijay; Takele, Robel (Elsevier, 2023)
China and India are the two top consumers of fertilizer nitrogen (N) in the world not only to provide food security to 36% of the global population living in the two countries but also due to fertilizer-related government policies being followed during the last more than 50 years. Excessive fertilizer N use is now a cause of N-related environmental pollution as well as a concern for climate change. Nitrogen use efficiency (NUE) at farmers' fields dictates both production of food crops as well as loss of N to the environment including efforts to curb climate change due to N2O emission. We used a gridded database on N input and N output for wheat, rice, and maize in China and India from 1961 to 2013 to synthesize the dynamics of NUE (percentage of applied N used by the crop) and surplus N (difference between total N input and N output) and in the light of relevant literature interpreted it in terms of past and future fertilizer N management scenarios and fertilizer related policies in the two countries. From 1961 to 2013, the percentage of fertilizer N in total N input in cereal crop production increased from 8–10% to 71–75% in India and from 30–37% to 80–84% in China. In both India and China, NUE has been continuously declining and in 2013 it was in the range of 20–24% (except 32% for wheat in India) due to several-fold increases in fertilizer N use and imbalanced use of fertilizer nutrients (particularly in India)—a consequence of huge subsidies provided by the governments on different fertilizer products. Estimates of maximum N output in the form of crop yield at saturating N input regimes determined from trajectories of N output as a function of total N input for 1961–2013 and 2001–13 revealed that crop and fertilizer N management for rice, wheat, and maize in India and China did not improve significantly since the Green Revolution era. As a large number of studies in India and China show that NUE can be increased by the advancement of technology front in terms of crop and fertilizer management and by reducing the fertilizer N rate without a significant reduction in the yield of crops, recommendations have been given for governments (to frame suitable policies), farmers, extension agencies, and fertilizer dealers.